Albie Sachs, heavily wounded in a bomb attack, during a press conference at Maputo Central Hospital, before leaving for London - Mueche, Alfredo,
Albie Sachs, heavily wounded in a bomb attack, during a press conference at Maputo Central Hospital, before leaving for London.